Penentuan Batas Pit Tambang Terbuka Bijih Nikel Berbasis Estimasi Cadangan Inverse Distance Weighting Menggunakan Surpac - muhammad ikmal; Ruth Bunga Ranggu; Muh Arif Idhan (Journal Teknik Dan Teknologi, 2026)
This study aims to determine the estimated reserves of lateritic nickel ore and to define the open pit mining boundary based on the obtained estimation results at Block III Batuawu, PT. Tambang Bumi Sulawesi. The reserve estimation was carried out using the Inverse Distance Weighting (IDW) method in Surpac 6.3 software by utilizing drilling data including assay, collar, geology, and survey data. The research stages consisted of database processing, ore body block modeling, application of Cut Off Grade (COG), and open pit design. The results show that the total resource is 1,369,191 tons with an average grade of 1.03% Ni and 31.56% Fe. After applying a COG of 1.3%, an extractable reserve of 404,771 tons was obtained with an average grade of 1.52% Ni and 21.55% Fe. Based on these results, an open pit design was developed with geotechnical parameters of 6 m bench height, 3 m bench width, and 55° slope angle, covering an area of 9.81 Ha with elevation ranges of 38.4–124.4 m. The required overburden removal is 964,421 tons with a stripping ratio of 1.6 : 1, indicating economically feasible mining conditions.